Karakteristik Anemia pada Sapi Bali di Daerah Klungkung Berdasarkan Morfologi Eritrositnya (CHARACTERISTIC ANEMIA OF BALI CATTLE IN KLUNGKUNG BASED ON ERYTROCYTE MORPHOLOGY) - Iwan Haryono Utama; Anak Agung Sagung Kendran; I Gusti Ngurah Badiwangsa; Ketut Suartini (Faculty of Veterinary Medicine, Udayana University and Published in collaboration with the Indonesia Veterinarian Association, 2001)
Karakteristik Anemia pada Sapi Bali di Daerah Klungkung Berdasarkan Morfologi Eritrositnya (CHARACTERISTIC ANEMIA OF BALI CATTLE IN KLUNGKUNG BASED ON ERYTROCYTE MORPHOLOGY)